2004
DOI: 10.1002/mds.20295
|View full text |Cite
|
Sign up to set email alerts
|

Short latency afferent inhibition and facilitation in patients with writer's cramp

Abstract: Patients with writer's cramp (WC) show abnormalities of sensorimotor integration possibly contributing to their motor deficit. We studied sensorimotor integration by determining short-latency afferent inhibition (SAI) in 12 WC patients and 10 age-matched healthy controls. A conditioning electrical median nerve stimulus was followed 14 to 36 msec later by transcranial magnetic stimulation of the contralateral primary motor cortex, and motor evoked potentials (MEP) were recorded from the relaxed or contracting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…In line with these clinical findings, application of a sensory alleviating maneuver in CD patients significantly reduced increased intracortical M1 facilitation [8]. Additionally, several studies indicated abnormal processing of somatosensory stimuli in dystonia leading to alterations of sensorimotor integration [9,10]. Previous studies also suggest that somatotopical organization and plasticity of the sensorimotor system are impaired in dystonia [2,3,11,12].…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…In line with these clinical findings, application of a sensory alleviating maneuver in CD patients significantly reduced increased intracortical M1 facilitation [8]. Additionally, several studies indicated abnormal processing of somatosensory stimuli in dystonia leading to alterations of sensorimotor integration [9,10]. Previous studies also suggest that somatotopical organization and plasticity of the sensorimotor system are impaired in dystonia [2,3,11,12].…”
Section: Introductionmentioning
confidence: 50%
“…These divergent findings may either be due to methodological differences, small sample size or different clinical characteristics. Impaired SAI in CD is in contrast to WC patients in whom SAI has been shown to be normal [10,12,13]. Apart from obvious clinical differences between CD and WC in terms of dystonia distribution, onset age and gender [33] one principal group difference relates to the fact that neurophysiological measurements were carried out in a non-dystonic state with the arms at rest in WC but with neck dystonia being present in CD.…”
Section: Sensorimotor Integrationmentioning
confidence: 87%
“…However, these alterations may also in some circumstances, such as after an injury or the sustained performance of repetitive muscular activity, become maladaptive plastic changes that are thought to be responsible for initiating and perpetuating certain movement disorders and chronic pain syndromes. 24,[39][40][41][42][43][44][45][46][47][48][49][50][51] Furthermore, joint dysfunction originating from an injury may be a cause of ongoing pain and loss of function due to maladaptive sensorimotor integration from a hyperafferentiation of the CNS from the dysfunctional joints and associated structures. [52][53][54][55][56][57][58] Does Repetitive Muscular Activity and Joint Dysfunction Lead to Maladaptive Plasticity?…”
Section: Clinical and Research Implicationsmentioning
confidence: 98%
“…The induced current flow was biphasic with a posterior-anterior direction. Pulses were delivered over the optimal position to elicit a maximal electromyographic (EMG) response of the controlateral abductor pollicis brevis (APB) muscle to conform to afferent inhibition paradigms (Kessler et al, 2005). The EMG signal was amplified using a Powerlab 4/30 system (ADInstruments, Colorado Springs, CO), filtered with a band pass 20-1000 Hz and digitized at a sampling rate of 4 KHz.…”
Section: Tms Recordingsmentioning
confidence: 99%